nanoDSF: In vitro Label-Free Method to Monitor Picornavirus Uncoating and Test Compounds Affecting Particle Stability - Real-Hohn, Antonio; Groznica, Martin; Löffler, Nadine; Blaas, Dieter; Kowalski, Heinrich (Frontiers in Microbiology, 2020)
Thermal shift assays measure the stability of macromolecules and macromolecular assemblies as a function of temperature. The Particle Stability Thermal Release Assay (PaSTRy) of picornaviruses is based on probes becoming strongly fluorescent upon binding to hydrophobic patches of the protein capsid (e.g. SYPRO Orange) or to the viral RNA genome (e.g. SYTO-82) that become exposed upon heating virus particles. PaSTRy has been exploited for studying the stability of viral mutants, viral uncoating, and the effect of capsid-stabilizing compounds. While the results were usually robust, the thermal shift assay with SYPRO Orange is sensitive to surfactants and EDTA and failed at least to correctly report the effect of excipients on an inactivated poliovirus 3 vaccine. Furthermore, interactions between the probe and capsid binding antivirals as well as mutual competition for binding sites cannot be excluded. To overcome these caveats, we assessed differential scanning fluorimetry with a nanoDSF device as a label-free alternative. NanoDSF monitors the changes in the intrinsic tryptophan fluorescence (ITF) resulting from alterations of the 3D-structure of proteins as a function of the temperature. Using rhinovirus A2 as a model, we demonstrate that nanoDFS is well suited for recording the temperature-dependence of conformational changes associated with viral uncoating with minute amounts of sample. We compare it with orthogonal methods and correlate the increase in viral RNA exposure with PaSTRy measurements. Importantly, nanoDSF correctly identified the thermal stabilization of RV-A2 by pleconaril, a prototypic pocket-binding antiviral compound. NanoDFS is thus a label-free, high throughput-customizable, attractive alternative for the discovery of capsid-binding compounds impacting on viral stability.